Upaya Peningkatan Writing Siswa Melalui Strategi Gambar - Khudriyah, Khudriyah; Munir, Nur (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
: In the era of globalisation, English has become an international communication tool used in various aspects of life, such as access to digital information, the workplace, and cross-cultural interactions. Therefore, senior high school students need to be equipped with English writing skills as one of the important productive skills. This mentoring activity aims to improve students' writing skills through picture-based writing strategies. This strategy is implemented using a process writing approach, which includes the stages of pre-writing, drafting, revising, and editing. The results of the mentoring programme show a significant improvement in students' writing skills. Based on the results of the paired sample t-test, the average score before the mentoring programme was 34.57, increasing to 55.43 after the mentoring programme. Additionally, the calculated t-value of 16.269 was greater than the table t-value of 2.0738, indicating a statistically significant difference. These findings suggest that the picture-based writing strategy is effective in improving students' writing skills. This strategy can serve as an innovative alternative in English language instruction at the madrasah level to make it more contextual, engaging, and aligned with students' needs.